Market Networking and Trading: A Case of Transforming Village Women’s Lives - Chiong-Javier, Ma. Elena (Social Sciences and Development Review, 2013)
An informal group of rural women residing in a Southern Philippine watershed community demonstrates that networking and market participation are viable means for self-transformation amidst limited opportunities. Based on network analysis and qualitative interviews, this article delineates the women’s marketing ties and experiences as vegetable biyahidors (traders) who hurdle constraints such as capital shortage, losses incurred from grading and transporting perishables, increasing market competition, and lack of organized response to problem solving. These challenges are addressed through marketing practices established individually, as well as collectively. The article underscores the necessity of institutional support through responsive market policies and programs to ensure the sustainability of the women’s entrepreneurial endeavors.